The Neptune Project - Holyoke, Polly (Disney/Hyperion Books, 2014)
No one asked Nere if she wanted to become a science experiment--they just went right ahead and bio-engineered her lungs to be able to breath water as well as air. She and a group of other genetically modified kids find out they are part of "The Neptune Project," which aims at creating a new human society in the ocean, far away from the dangers of land. However, the dangers of the sea are just as deadly.